La politique éducative de l’Espagne dans le Nord du Maroc pendant la période du Protectorat (1912-1956) - Irene González González (Revue des Mondes Musulmans et de la Méditerranée, 2014)
After the establishment of the protectorate, the Spanish colonial government set up a diversified education system for children of Spanish families who began to settle in the protectorate and, secondarily, for the Moroccan population of Muslim and Jewish faith. The colonial authorities viewed educating the Moroccans as a means to exert political and social control over both the population and the territory. The role of the school as a colonial instrument began to be strengthened during the period of political-military instability (1912-1927) by means of a “Spanish-Arab educational model”, which followed the example implemented by the French in their Algerian colony starting in the mid-19th century. The Francist government transformed the Spanish-Arab educational model into a Moroccan model through a process of Moroccanizing the teaching paradigm, subjects, language and teachers.